2016
DOI: 10.1021/acs.biomac.6b00696
|View full text |Cite
|
Sign up to set email alerts
|

On cellulose dissolution and aggregation in aqueous tetrabutylammonium hydroxide

Abstract: Aqueous tetrabutylammonium hydroxide, TBAH(aq), has been found to dissolve cellulose and to be a potential solvent for chemical processing or fiber spinning. In this paper, we have investigated the dissolution state of cellulose in 40 wt % TBAH(aq) solvent, and present an extensive study of rheology, combined with static light and small-angle X-ray scattering, to correlate cellulose aggregation with changes in the rheological parameters. Two cellulose molecular weights are compared. Microcrystalline cellulose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 44 publications
6
40
0
1
Order By: Relevance
“…For lower q-values, the scattered intensity is significantly higher compared to what is predicted by the PSM. This shows that the cellulose molecules form aggregates, again similar to what was previously observed in aqueous tetrabutylammonium hydroxide solvent (Behrens et al 2016;Gubitosi et al 2016). The green curve in Fig.…”
Section: Saxssupporting
confidence: 85%
See 2 more Smart Citations
“…For lower q-values, the scattered intensity is significantly higher compared to what is predicted by the PSM. This shows that the cellulose molecules form aggregates, again similar to what was previously observed in aqueous tetrabutylammonium hydroxide solvent (Behrens et al 2016;Gubitosi et al 2016). The green curve in Fig.…”
Section: Saxssupporting
confidence: 85%
“…8 and previously published scattering curves for the TBAH/water system (Behrens et al 2016;Gubitosi et al 2016). Essentially, the solvation sheath of TBA þ ions around the cellulose molecules is found in both systems, which indicates the presence of charge on the cellulose chains.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…[41][42][43][44] -After dissolution of native cellulose (cellulose I), which is metastable, one typically observes gelation, which is due to cellulose aggregation and the onset of precipitation of (stable) cellulose II. 45,46 The fact that gelation is significantly reduced in the presence of surfactants points to the presence of hydrophobic parts.…”
Section: Hydrogen Bonding Vs Hydrophobic Interactionsmentioning
confidence: 99%
“…Recently we have characterized the dissolution state of microcrystalline cellulose, MCC, in the related solvent, 40 wt% tetrabutyl ammonium hydroxide in water, TBAH(aq) (Gubitosi et al 2016;Gentile and Olsson 2016;Behrens et al 2016). It was found that the cellulose was molecularly dissolved, with effectively repulsive cellulose-cellulose interactions at concentrations lower than ca.…”
Section: Introductionmentioning
confidence: 99%